Heart rate response to ultraendurance cycling - Neumayr, G.; Pfister, R.; Mitterbauer, G.; Gaenzer, H.; Sturm, W.; Hoertnagl, H. (British Journal of Sports Medicine, 2003)
The heart rate (HR) response to ultraendurance cycling is poorly understood. This case report describes the exercise intensity of ultraendurance cycling by means of HR monitoring in a well trained male amateur cyclist performing the Ötztal Radmarathon twice en bloque in a circuit of two identical laps (distance 460 km; cumulative altitude difference 11 000 m). The overall intensity was moderate (HRmean = 130 beats/min; HRmean/HRmax = 0.71) corresponding to an average individual workload of 47% of VO2MAX. Almost the whole race was performed under aerobic conditions (99.6%); high intensity work was negligible (0.4%). The average speed and the HR response also declined in the course of the two laps, average speed by 17.2% (23.8 to 19.7 km/h), HRmean by 10.1% (138 to 124 beats/min), and HRmean/HRmax by 10.7% (0.75 to 0.67). This scale of HR decrease corresponds to comparable data gained in the field of triathlon and represents a specific cardiac feature of ultraendurance exercise in general.